A Party with Purpose: To Strengthen the Role of Women in Politics program (1976)
This brochure promotes "A Party With a Purpose", an event held to strengthen the role of women in politics by supporting the National Women's Political Caucus (NWPC), its Democratic Task Force, and the Democratic Women's Agenda (DWA '76). It explains that the NWPC organizes women nationwide to increase political participation, expand influence within the Democratic Party, and advance women's issues in the party platform during the 1976 convention year. The program features prominent political leaders and activists—including members of Congress, party leaders, and Governor Jimmy Carter—with Candice Bergen serving as emcee. The brochure concludes with an extensive list of sponsors and organizing committee members, highlighting broad support from national political, labor, and feminist leaders.